E-Banking Instruments and Service Delivery of Commercial Banks in Nigeria: Evidence from United Bank of Africa, Ilaro Branch, Nigeria - Olayiwola, Habeeb Olaniyi; Olorunyomi, Hannah Oluwakanyinsola (The Indonesian Institute of Science and Technology Research, 2025)
This study investigated the impact of e-banking tools on service delivery of commercial banks in Nigeria with reference to United Bank of Africa (UBA) Ilaro branch. The study adopted a simple random sampling technique and also collected data through online questionnaires sent to the customers and staff of UBA Ilaro. Eighty Google Form/online questionnaires were filled and retrieved from the respondents. The responses were sorted, coded and analyzed using descriptive and inferential statistics such as regression analysis via SPSS software. The results of descriptive statistics show that all the e-banking instruments are very important in delivering quality services of commercial banks, especially UBA Ilaro branch. From the regression results, it was found that automated teller machine and mobile banking have positive and significant impact on service delivery of UBA Ilaro branch. Although point of sale also had positive relationship with service delivery but it is not statistically significant at 5% critical value. The study concluded that among the instruments of e-banking, automated teller machine and mobile banking services are the essential tools to achieve effective service delivery of UBA Ilaro branch. It was therefore recommended that the Branch Manager should ensure that the ATMs are adequately funded on a consistent basis to provide quality services to their customers. Generally, the government through its agency should ensure optimization of Internet Bandwidth allocation to tackle the problem of internet failure across the country.